AB0346 TREND OVER TIME OF AORTIC STIFFNESS IN RHEUMATOID ARTHRITISPATIENTS AND ITS RELATION WITH CARDIOVASCULAR EVENTS. (June 2019) - Orsolini, Giovanni; Cioffi, Giovanni; Giollo, Alessandro; Ognibeni, Federica; Dalbeni, Andrea; Gatti, Davide; Fassio, Angelo; Bonasera, Giulia; Rossini, Maurizio; Viapiana, Ombretta
Abstract : Background: Ascending aorta has an increased stiffness (AoSI) in rheumatoid arthritis (RA) patients due to their chronic inflammatory status. We assessed prevalence and modification of AoSI during a follow up period and its prognostic role on cardiovascular events (CVE) in a large cohort of RA patients Objectives: Prognostic role of AoSI and its modification over time on CVE. Methods: We prospectively followed 146 RA patients without overt cardiac disease with periodic echocardiographic examination. Abnormally high AoSI was diagnosed if AoSI > 6.07% (95th percentile of the AoSI detected in our reference healthy population). AoSI was assessed at the level of the aortic root by two-dimensional guided M-mode evaluation as part of a thorough echocardiography performed in all patients. CVE information were collected during follow up Results: Of our 146 RA patients, 89 had a normal AoSI at baseline, in the remaining 57 it was abnormally high. After a mean follow up of 27 months: among patients with normal baseline AoSI it stayed normal in 64 (6 to 5, 6%) and in 25 raised to an abnormal high AoSI (from 3, 7 to 11, 9%); of the 57 patients with high baseline AoSI, 33 went back to normal values (9, 4 to 3, 1%) and in 24 it remained high. Of these 4 groups divided by AoSI trend over time the group with de novo high AoSI showed the highest prevalence of new CVE (33%), together with the group with persistent high AoSI (16%). Much lower prevalence was observed in the other two groups (persistent normal 5%, normalized at follow up 6%). Conclusion: Abnormally high AoSI is common in RA patients, rapid increase through time or persistent high AoSI identify those patients that are more prone to develop CVE. On the contrary, patients that showed a normalization of AoSI demonstrated to have a similar low incidence of CVE as patients who ever had a normal AoSI. Disclosure of Interests: Giovanni Orsolini Speakers bureau: Grunenthal, Giovanni Cioffi: None declared, Alessandro Giollo: None declared, Federica Ognibeni: None declared, Andrea Dalbeni: None declared, Davide Gatti Speakers bureau: Abiogen, Amgen, Janssen-Cilag, Mundipharma, Pfeizer, Angelo Fassio Speakers bureau: Abiogen Pharma, Giulia Bonasera: None declared, Maurizio Rossini: None declared, Ombretta Viapiana Speakers bureau: Novartis, Abbvie, Eli-Lilly, Sanofi Genzyme